The Impact of Clearance in the Front -wheel Steering Mechanism on Response Delay and Trajectory Deviation - Lv, Mingzhen (Exploring Science Academic Conference Series, 2026)
Single Pilot Operation (SPO) imposes stringent safety requirements on aircraft ground taxiing. However, the quantitative impact of mechanical clearance in the nose -wheel steering mechanism on response delay, trajectory deviation, and pilot workload remains insufficiently explored. In this study, a multi-body kinematic model with varying clearances was established using ADAMS to investigate this mechanism. By integrating a bicycle kinematic model, the strut steering angles were translated into aircraft taxiing trajectories under both open-loop and closed -loop (proportional control) conditions. The results demonstrate a non -linear positive correlation between clearance size and response delay. Crucially, automatic control exhibits an inherent compensation boundary, failing to eliminate the initial lag caused by the mechanical dead zone. Trajectory deviations, including lateral offset and heading angle errors, expand significantly with larger clearances and are further amplified at higher taxiing speeds. Workloa d assessments indicate that the 0.5 mm clearance (defined maintenance threshold in this paper) already induces a high monitoring workload for single pilots. Consequently, this paper recommends stricter maintenance thresholds, feedforward compensation strat egies, and predictive heading indicators to ensure taxiing safety and alleviate pilot workload in SPO mode.